Engraftment of self-renewing endometrial epithelial organoids promotes endometrial regeneration by differentiating into functional glands in rats - Ma, Yana; Qian, Jingjing; Xu, Xin; Wei, Cheng; Wang, Minyuan; Zhang, Peipei; Chen, Sijia; Zhang, Lingyan; Zhang, Yanling; Wang, Yanpeng; Xu, Wenzhi; Liu, Mengying; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Extensive trauma frequently disrupts endometrial regeneration by diminishing endometrial stem cells/progenitor cells, affecting female fertility. While bone marrow mesenchymal stem cell (BMSC) transplantation has been suggested as an approach to address endometrial injury, it comes with certain limitations. Recent advancements in endometrial epithelial organoids (EEOs) have displayed encouraging potential for endometrial regeneration. Therefore, this study aims to explore whether EEOs surpass BMSCs in their ability to repair injured endometrium and to examine whether the restoration process involves the integration of EEOs into the endometrial tissue of the recipient. Methods We developed rat EEOs (rEEOs) mimicking the features of the rat endometrium. Subsequently, we created a rat model of endometrial injury to compare the effects of rEEOs and rat BMSCs (rBMSCs) on endometrial regeneration and reproductive recovery. Bulk RNA-sequencing analysis was conducted to further investigate the capacity of rEEOs for endometrial regeneration and to identify discrepancies between rEEOs and rBMSCs. Additionally, to track the fate of the transplanted cells in vivo, we transplanted green fluorescent protein (GFP) -labelled rEEOs or red fluorescent protein (RFP) -labelled rBMSCs. Results In a rat model of endometrial injury, we observed that fertility recovery in rats transplanted with rEEOs was more comparable to that of normal rats than in those treated with rBMSC. rEEOs possess a high concentration of endometrial epithelial stem/progenitor cells and secrete vascular endothelial growth factor (VEGF)-A to promote endometrial neovascularization. Significantly, we observed that cells from GFP-labelled rEEOs could integrate and differentiate into functional glands within the injured endometrium of recipient rats. Discussion EEOs offer a transformative approach to address the challenges of endometrial trauma. Their remarkable regenerative potential holds promise for the restoration of damaged endometrium. As we venture into the future, the concept of utilizing patient-specific EEOs for transplantation emerges as a tantalizing prospect. However, the EEOs in our experiments were mainly cultured in Matrigel, which has barriers to clinical translation as a biomaterial, a new biomaterial to be explored. Secondly, our experiments have been successful only in rat models, and more efforts need to be made before clinical translation.